2020
DOI: 10.1371/journal.pone.0240134
|View full text |Cite
|
Sign up to set email alerts
|

Methodological variations affect the release of VEGF in vitro and fibrinolysis’ time from platelet concentrates

Abstract: Blood Concentrates (BCs) are autologous non-transfusional therapeutical preparations with biological properties applied in tissue regeneration. These BCs differ in the preparation method, in fibrin network architecture, growth factors release as well as in platelet/cell content. Methodological changes result in distinct matrices that can compromise their clinical effectiveness. The present study evaluated the influence of different g-forces and types of tubes in the release of vascular endothelial growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…The three-dimensional arrangement of the fibrin matrix favors cell transit allowing the progenitor cells from the bone marrow to be integrated into the graft set, constituting the tripod of tissue engineering. (20,21) In the clinical case presented, there was a 4mm reduction in the probing depth and no bleeding after probing.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The three-dimensional arrangement of the fibrin matrix favors cell transit allowing the progenitor cells from the bone marrow to be integrated into the graft set, constituting the tripod of tissue engineering. (20,21) In the clinical case presented, there was a 4mm reduction in the probing depth and no bleeding after probing.…”
Section: Discussionmentioning
confidence: 84%
“…Studies have not shown the effectiveness of any of these regeneration materials over others. (18) In the present clinical case, the granules of the synthetic hydroxyapatite (Cerasorb M®) hydrated with a solution of piperacillin / tazobactam was mixed with liquid phase platelet-rich fibrin (20) . The objective was to promote the initial stability and the continuous release of antibiotics for the biomaterial and the environment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[ 18 ] Otherwise, is known that the time and force performed in the centrifugation can influence the characteristics of the membrane that will be applied in the surgical receptor area. [ 8 19 ]…”
Section: Discussionmentioning
confidence: 99%